SOME ASPECTS OF EFFECTIVENESS AND SAFETY OF ANTIBACTERIAL DRUGS IN PREGNANCY - D. Y. Zhukova; G. N. Kovalskaya; S. V. Ionoushene (Acta Biomedica Scientifica, 2012)
Analysis of published data on clinical effectiveness and safety of antimicrobial drugs indicates that original and generic antibacterial medicines sometimes significantly differ in the therapeutic equivalence and in the frequency and severity of side effects.